Preparação, caracterização e aplicação de filmes finos tipo LbL a base de N,N,N-trimetilquitosana e Heparina - Follmann, Heveline Dal Magro (2014)
N-quaternized derivatives of chitosan (DMC and TMCs) were synthesized using different methods and their chemical structures were characterized. Two N,N,Ntrimethyl chitosan (TMC) with O-methylated groups were prepared and showed degree of quaternization (DQ) equal to 20 and 80%. O-methyl free TMC was obtained from N,N-dimethyl chitosan (DMC) and presented DQ = 25%. All the derivatives were used to obtain LbL thin films with heparin (HEP). The films were characterized and submitted to some applications and the efficiencies of the systems were evaluated. TMC20/HEP and TMC80/HEP thin films prepared at different pHs were submitted to biological assays. Assays against E. coli showed that the bacterial adhesion on the films surface was reduced. Antibacterial assays showed that the TMC80/HEP system prepared at pH 7.4 had effective bactericidal activity. In vitro controlled release of HEP, evaluated in simulated intestinal fluid (SIF) and simulated gastric fluid (SGF), showed that the release of HEP is strongly pronounced in SIF medium due to ionization of -NH2, -NHCH3 and -N(CH3)2 groups. In a second step of this work, the DMC and O-methyl free TMC were used to obtain thin films prepared by different LbL deposition methods (immersion, spray and spin-coating). After appropriated characterization, the films were submitted to cellular assays using NIH/3T3 fibroblasts. The results showed that N-trimethylation has a positive effect on cell proliferation. The films prepared by immersion method showed better results regarding cell viability